How public are public affairs program defining and redefining the public in the TV program Wisk Ko Lang - Pulongbarit, Roni Rose Damian 1990-
"This study looks at the 'publicness' of Wish Ko Lang as a public affairs program. It uses political economy as a framework to study how the program commodifies the help it gives. It tries to answer the title of the research, how public are public affairs program? Libre ang mangarap, this is the tagline of Wish Ko Lang, a wish-giving show in Philippine television. The program is a self-proclaimed public affairs program which airs on GMa-7 every Saturday, from five to six in the afternoon. Since 2002, Wish Ko Lang has been granting wishes such as family reunions, dream weddings, fan-meets-idol, second chances for old stars, medical treatments, and scholarship programs for physically challenges and deserving individuals. As the theme song of the program says, 'Walang Imposible', Wish Ko Lang is trying to grant all kinds of wishes from almost anyone from anywhere in the Philippines. Interestingly, Wish Ko Lang, although a public affairs program which is supposed to be informative and non-commercial, is actually and very evidently commercialized. The study used two research methods. The first was a textual analysis of the program. The program is analyzed and assessed first by watching the product itself. Embedded in the program are a number of commercials and TV promotions of GMA shows and stars. The second method was an interview, specifically a single-issue testimony. It is a case study of two individuals whose wishes have been granted by Wish Ko Lang. The interviews tried to find out how the program was able to help the individual, if it did, and what happens to them after their wishes have been granted."